Near‐Infrared Reflection Modulation Through Electrical Tuning of Hybrid Graphene Metasurfaces. Issue 6 (30th January 2022) - Cai, Ziqiang; Liu, Yongmin
Abstract: Graphene, a 2D material with tunable optical properties, has recently attracted intense interest for reconfigurable metasurfaces. So far, the working wavelength of graphene‐based or hybrid graphene metasurfaces has been limited in the mid‐infrared and terahertz spectra. In this paper, by combining graphene with Au nanostructures, the authors demonstrate a near‐infrared tunable metasurface with decent modulation efficiency, weak dependence on graphene's carrier mobility, and small gate voltages, attributing to the unique interband transition of graphene. The experimental results agree well with numerical simulations. It is also shown that by properly designing the structural parameters of Au nanostructures, the hybrid graphene metasurface can be tunable in both near‐infrared and mid‐infrared regions. Abstract : A near‐infrared tunable graphene metasurface is demonstrated. It combines metallic plasmonic structures with graphene to enhance the interband transition of graphene, resulting in decent tunability and weak dependence on carrier mobility. The metasurface shows the potential for many applications, including near‐infrared electro‐optic modulators, reconfigurable lenses, and polarization modulators.